Secure Sockets Layer/Transport Layer Security for E-Commerce (International Journal of Scientific Research and Management (IJSRM), 2024)
Digital commerce has revolutionized the global economy, offering many opportunities for businesses and consumers. The increase in volume and number of online transactions comes the critical need for robust security measures to protect sensitive data from malicious actors. The research paper aims to provide stakeholders with the knowledge and insights necessary to build trust and confidence in online transactions. Specific objectives are: (i) to establish the fundamental principles underpinning Secure Sockets Layer/Transport Layer Security (SSL/TLS) encryption, (ii) to provide SSL/TLS mechanisms for securing online transactions and protecting sensitive customer information, (iii) to determine how SSL/TLS protocols establish secure communication channels between clients and servers, ensuring the confidentiality, integrity, and authenticity of data exchanged in digital marketplaces and (iv) to establish the effectiveness of SSL/TLS in safeguarding sensitive customer information and mitigating the cyber threats. The methodology used to achieve the objectives was a desktop survey. The outcome of the desktop survey includes the fundamental principles underpinning Secure Sockets Layer/Transport Layer Security (SSL/TLS) encryption, the SSL/TLS mechanisms for securing online transactions and protecting sensitive customer information, how SSL/TLS protocols establish secure communication channels between clients and servers, ensuring the confidentiality, integrity, and authenticity of data exchanged in digital marketplaces and the effectiveness of SSL/TLS in safeguarding sensitive customer information and mitigating the cyber threats